The Sequence of Prostaglandin-Endoperoxide Synthase 2 Gene in Women with Cervicitis - Maha A. Ahlial; Nazar Sh. Mohammed; Maysara S. Khalaf (Journal of Techniques)
Cervicitis is a clinical syndrome characterized by inflammation of primarily the columnar epithelium of the uterine endocervix. It can be acute or chronic. Prostaglandin endo peroxide synthase2 (Cyclooxygenase-2) is a key enzyme in prostaglandin synthesis, which is coded by the PTGS2 gene, and recognized as the master switch that activates the inflammatory response; its induction leads to the biosynthesis of prostaglandins.